Community-based psychoeducation for disaster preparedness: Improving resilience in rural West Sumatra - Renidayati, Renidayati; Astuti, Verra Widhi; Rachmadanur, N; Harahap, Nurlelasari; Darwel, Darwel (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2026)
Previous disaster preparedness studies in rural, disaster-prone areas have largely prioritized structural mitigation and early warning systems, leaving a critical gap in community-based health interventions that address psychosocial readiness. This study introduces a culturally contextualized psychoeducational intervention as a public health strategy to strengthen disaster preparedness in District of X Koto, Tanah Datar Regency, West Sumatra, Indonesia. The objective was to enhance community preparedness through an intervention emphasizing psychosocial health, risk perception, and self-efficacy as core components of disaster health interventions. A participatory intervention design was implemented over nine months (March–November 2024), involving 69 community members. The intervention comprised situational analysis, group-based psychoeducational sessions, disaster simulations, and pre- and post-test assessments. Results demonstrated a substantial improvement in overall preparedness scores, increasing from a mean of 12.54 to 37.64 after the intervention. Beyond cognitive gains, participants exhibited improved emotional regulation, heightened awareness of disaster risks, and stronger behavioral intentions to engage in adaptive response actions. These outcomes align with established psychosocial health theories, underscoring the effectiveness of community-centered learning in enhancing resilience. The intervention was particularly beneficial for participants with limited formal education, indicating its inclusivity and scalability. Integrating psychoeducational health interventions into disaster preparedness frameworks may strengthen public health resilience and support sustainable disaster risk reduction in rural and urban disaster-prone settings.